Answer:
1
[tex] \frac{2}{3} + \frac{1}{2} = \frac{4}{6} + \frac{3}{6} = \frac{5}{6} [/tex]
2
[tex] \frac{2}{5} + \frac{1}{10} = \frac{4}{10} + \frac{1}{10} = \frac{5}{10} \div 5 = \frac{1}{2} [/tex]
3
[tex] \frac{1}{5} + \frac{2}{4} = \frac{4}{20}+ \frac{10}{20} = \frac{14}{20} \div 2 = \frac{7}{10} [/tex]
4
[tex] \frac{3}{5} + \frac{3}{8} = \frac{24}{40} + \frac{15}{40} = \frac{39}{40} [/tex]
5
[tex] \frac{2}{7} + \frac{1}{4} = \frac{8}{28} + \frac{7}{28} = \frac{15}{28} [/tex]
6
[tex] \frac{3}{5} - \frac{3}{10} = \frac{6}{10} - \frac{3}{10} = \frac{3}{10} [/tex]
7
[tex] \frac{4}{6} - \frac{1}{12} = \frac{8}{12} - \frac{1}{12} = \frac{7}{12} [/tex]
8
[tex] \frac{4}{6} - \frac{1}{2} = \frac{4}{6} - \frac{3}{6} = \frac{1}{6} [/tex]
9
[tex] \frac{3}{4} - \frac{1}{3} = \frac{9}{12} - \frac{4}{12} = \frac{5}{12} [/tex]
10
[tex] \frac{7}{8} - \frac{3}{4} = \frac{7}{8} - \frac{6}{8} = \frac{1}{8} [/tex]
Step-by-step explanation:
Sana makatulong☺️
pa brainliest po☺️